2002
DOI: 10.1515/cclm.2002.051
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Elastase-1 as a Test for Pancreatic Function: a Review

Abstract: Pancreatic elastase-1 is a specific human protease synthetized by the acinar cells. Immunoreactive elastase-1 cannot be detected in either porcine or bovine pancreatic enzyme preparations. It is very stable and, in contrast to fecal chymotrypsin, elastase is unaffected by exogenous pancreatic enzyme treatment, and correlates well with exocrine pancreatic function tests. The measurement of this proteolytic enzyme in stool by means of an enzyme-linked immunosorbent assay (ELISA) is a sensitive, specific, and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 44 publications
0
28
0
2
Order By: Relevance
“…Results are reported as microgram per gram of stool. The lower detection limit is 15 μg/g 17. The cost of analysis is approximately £26, and turnaround time is approximately 21 days.…”
Section: Techniquementioning
confidence: 99%
“…Results are reported as microgram per gram of stool. The lower detection limit is 15 μg/g 17. The cost of analysis is approximately £26, and turnaround time is approximately 21 days.…”
Section: Techniquementioning
confidence: 99%
“…They found that, using a < 200 Ag/g cut-off, the test had an overall 93% sensitivity and 93% specificity. Limits of analytical sensitivity are not well defined, but a detection limit of 15 Ag/g is generally reported [12]. Soldan et al compared 16 CF patients with established pancreatic insufficiency by the secretin -pancreozymin test to 23 healthy controls and found that, using the standard cut-off of 200 Ag/g of stool for E1, they had a 96% specificity and 100% sensitivity for detection of pancreatic insufficiency [13].…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…Thus, E1 appears to have some advantages over fecal chymotrypsin in detection of pancreatic insufficiency in that it has comparable if not better sensitivity, depending on the cut-off values used. E1 is very stable in stool samples and can be estimated even in patients on pancreatic enzyme supplements without need for their discontinuation [12].…”
Section: Comparison With Fecal Chymotrypsinmentioning
confidence: 99%
“…Evaluation of human pancreatic fecal elastase-1 (FE-1) in the stool is currently the most reliable and sensitive non-invasive procedure for the diagnosis of PI, with a sensitivity ranging from 54 to 95% and a specificity of approximately 80% [7][8][9][10][11]. A commercial enzyme-linked immuno-sorbent assay (ELISA) method is currently available to measure FE-1 concentration in stool samples, thus providing the potential for a simple, reliable, and noninvasive evaluation of pancreatic function in IBD patients [10].…”
Section: Introductionmentioning
confidence: 99%